Comparison of direct digital and conventional imaging with Ekta Speed Plus and INSIGHT films for the detection of approximal caries - De Araujo, Elaine Aparecida Félix [UNESP]; De Melo Castilho, Julio Cezar [UNESP]; Medici Filho, Edmundo [UNESP]; De Moraes, Mari Eli Leonelli [UNESP] (My University, 2005)
Purpose: To evaluate the accuracy of approximal caries detection comparing enhanced and unenhanced Sidexis CCD-based digital image with Ektaspeed Plus and INSIGHT films. Methods: Fifty-two extracted premolars were imaged under identical standardized geometric and exposure conditions. Four observers, using five points confidence scale, rated 104 approximal surfaces for the presence or absence of carious lesions by means of four image modalities: (1) observer enhanced; (2) unenhanced Sidexis displays; (3) E speed films and (4) F speed film. Histologic sections served as validating criterion for the presence and depth of carious lesions. Diagnostic accuracy was measured as the area beneath the ROC curve. Results: Mean ROC (receiver operating characteristic) curve areas for approximal surfaces were 0.865 (E speed), 0.856 (F speed), 0.816 (unenhanced Sidexis) and 0.776 (observer enhanced). There were no significant differences between unenhanced digital Sidexis and films. Observer enhanced Sidexis images exhibited a statistically significant lower diagnostic accuracy than the film images for two of the observers.